1977
DOI: 10.1083/jcb.75.3.788
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-cell communication and myogenesis.

Abstract: Cell-to-cell communication was characterized in prefusion chick embryo myoblast cultures, and it was determined that the prefusion myoblasts can interact via gap junctions, ionic coupling, and metabolic coupling. The biological relevance of this communication was supported by the detection of gap junctions between myoblasts in embryonic muscle. Communication was also examined in fusionarrested cultures to determine its potential relationship to fusion competency. In cultures that were fusion arrested by treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
56
0

Year Published

1980
1980
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 51 publications
3
56
0
Order By: Relevance
“…In the present study, we contributed to shed some light on this issue, by showing that TRPC1 channel activity is required for the up-regulation of Cx43 expression elicited by S1P in skeletal myoblasts. The physiological significance of this interaction in skeletal myogenesis is consistent with the well-known role of Cx43 in synchronizing cell differentiation among contacting myoblasts [6,25,48], and in making them competent for syncytial fusion [6,25,49,50]. In particular, we have shown that the functional link between TRPC1 and Cx43 protein in S1P-differentiating myoblasts involves the activation of m-calpain/classical PKCs axis, thus contributing to extend our knowledge on the molecular mechanisms by which S1P exerts its pro-myogenic action.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, we contributed to shed some light on this issue, by showing that TRPC1 channel activity is required for the up-regulation of Cx43 expression elicited by S1P in skeletal myoblasts. The physiological significance of this interaction in skeletal myogenesis is consistent with the well-known role of Cx43 in synchronizing cell differentiation among contacting myoblasts [6,25,48], and in making them competent for syncytial fusion [6,25,49,50]. In particular, we have shown that the functional link between TRPC1 and Cx43 protein in S1P-differentiating myoblasts involves the activation of m-calpain/classical PKCs axis, thus contributing to extend our knowledge on the molecular mechanisms by which S1P exerts its pro-myogenic action.…”
Section: Discussionsupporting
confidence: 78%
“…There are various reports of ultrastructural alterations during myogenesis that have been described from thin section (8,13,14,17,22,29) and freeze-fracture (8,14,23) electron microscopies. Our results show that apposed myoblast membranes fuse at several points and that their cytoplasms are continuous through pores that exist between the long vesicles seen in thin section preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrastructural studies of developing skeletal muscle have provided the basis for the current interest in localized membrane events that are associated with myoblast fusion (8,13,14,17,22,29). An initial event in the overt development of muscle tissue in culture is the fusion of the plasma membranes of neighboring mononucleated myoblasts to form multinucleated myotuves.…”
mentioning
confidence: 99%
“…In the differentiation of segmental myotomes, unsegmented mesodermal cells communicate with each other, then separate during morphogenetic movements (Hayes, 1975;Blackshaw and Warner, 1976). Myoblasts at pre-fusion stages are also capable of forming gap junctions, if given the opportunity for close association in vitro (Chow and Young, 1987;Kalderon et al, 1977). At later stages myotubes containing fully differentiated myofibrils are again connected, but become fully distinct functional units in coincidence with innervation and in a manner dependent on activity (Keeter et al, 1975;Dennis, 1981;Dennis et al, 1981;Armstrong et al, 1983).…”
Section: Quantitation Of Gap Junctionsmentioning
confidence: 99%
“…Even though some association was found between gap junction presence and cell fusion (Rash and Staehelin, 1974;Rash an Fambrough, 19731, it is clear that in most cases the two are not causally related (Kalderon et al, 1977;KaYderon andGilula, 1979, see Cavaney, 1985).…”
Section: Quantitation Of Gap Junctionsmentioning
confidence: 99%